2018
DOI: 10.1021/acsaem.8b00474
|View full text |Cite
|
Sign up to set email alerts
|

Abundance and Speciation of Surface Oxygen on Nanosized Platinum Catalysts and Effect on Catalytic Activity

Abstract: Oxygen at the surface of nanosized platinum has a direct effect on catalytic activity of oxidation−reduction chemical reactions. However, the abundance and speciation of oxygen remain uncertain for platinum with different particle size and shape characteristics, which has hindered the development of fundamental property− activity relationships. We have characterized two commercially available platinum nanocatalysts known as Pt black and Pt nanopowder to evaluate the effects of synthesis and heating conditions … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 125 publications
1
13
0
Order By: Relevance
“…These conditions reconcile results from previous studies that could not be explained thus far. For example, heterogeneous metallic platinum is a good catalyst for H 2 O 2 decomposition. , However, this catalyst has never been successfully employed for the oxidative methane upgrade because platinum-catalyzed H 2 O 2 decomposition does not proceed via a radical-based mechanism. , Likewise, radiation-induced ·OH generation has been used to oxidize methane, but methanol was not present in the products, because step 3.2 does not occur in the absence of AuPd (Figure ). Similarly, Fenton catalysts decompose H 2 O 2 through a radical pathway and thus should catalyze the conversion of CH 4 to CH 3 OH.…”
Section: Resultsmentioning
confidence: 99%
“…These conditions reconcile results from previous studies that could not be explained thus far. For example, heterogeneous metallic platinum is a good catalyst for H 2 O 2 decomposition. , However, this catalyst has never been successfully employed for the oxidative methane upgrade because platinum-catalyzed H 2 O 2 decomposition does not proceed via a radical-based mechanism. , Likewise, radiation-induced ·OH generation has been used to oxidize methane, but methanol was not present in the products, because step 3.2 does not occur in the absence of AuPd (Figure ). Similarly, Fenton catalysts decompose H 2 O 2 through a radical pathway and thus should catalyze the conversion of CH 4 to CH 3 OH.…”
Section: Resultsmentioning
confidence: 99%
“…The first order effect of H 2 O 2 concentration in the rate of H 2 O 2 decomposition by AuPd nanocatalysts observed here is consistent with previous reports. This indicates that in the rate limiting step of the reaction one H 2 O 2 molecule reacts with one active site at a time. ,, This is important because from reactions –, it is anticipated that to form methanol one molecule of methane and one molecule of OH* must react together. Because radical species are unstable, in steady state, the rate of OH* formation and decomposition are equal (eq ), and the rate of methanol formation is proportional to the concentration of methane and OH* in solution (eq )­ …”
Section: Resultsmentioning
confidence: 99%
“…The elongation observed on Pt black crystallites occurs along random directions, and no particular crystallographic plane is preferentially exposed for either catalyst. When dispersed in aqueous solutions the crystallites of both catalyst samples are partly aggregated and the extent of aggregation is similar for both [ID am-2018-023446] …”
Section: Resultsmentioning
confidence: 99%
“…This article reports the rates of H 2 O 2 decomposition as a function of H 2 O 2 concentration, pH, and temperature by two common Pt nanocatalysts, known as Pt black and Pt nanopowder. Our characterization of these samples, which have different average crystal size and shape characteristics, revealed new information regarding the abundance and speciation of surface oxygen [ID am-2018-023446] . The results from this study showed that oxygen at the surfaces is primarily chemisorbed with platinum and that its abundance increases with increasing particle size.…”
Section: Introductionmentioning
confidence: 88%